Collective organization of practice in a Spanish elite soccer academy - Martinez-Santos, R.; Blanco-Villasenor, A.; Los-Arcos, A. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Any football academy is a complex system in which many agents must make lots of decisions (1) in a collaborative and goal oriented context. The so-called technical managers try to plan in the longer terms the most suitable practice for the elite-players-to-be. In this study we wondered how coherent coaches` intervention strategies were in relation to each other for a transversal period of seven formation years (U-14 to U19 levels). Methods Based on their diaries, we described the structure of the practice activities proposed by six coaches from the football academy of a Spanish Liga Club. In total, 20 006 min of training in 272 sessions were analyzed. Statistical procedures were made on SPSS 15.0, SAS 9.1.3 and Generalizability software by Ysewijin, (1996). Results & Discussion As expected, we found differences between the coaches as far as the practice they proposed was concerned. For instance, time spent in activities with or without collaboration and opposition was different between teams ( 2=942,36, p=0,000), but without any sense of progression. Furthermore, the analysis of variance components showed that the type of task (motor action domain) explained the 85% of the total variance of the model whereas the team explained just 5% on its own and 15% overall. Conclusion There did not seem to be a collective organization of practice apart from a common criterion about the principles for the design of activities.